Interview with Robert McCorkle and Mike Worth, October 2, 1971 (1971)
Interviewer with the Director of International Education, Robert McCorkle, and another administrator in International Education, Mike Worth [00:00:04] Subject: Cal Poly meets the challenge of international education [00:00:53] McCorkle describes the 3 parts of the International Education program, two on campus and 1 over seas [00:01:40] McCorkle talks about contract educational programs in Africa, Guatemala, and Thailand [00:02:50] Worth discusses the training of foreign participants that have been sent to Cal Poly by the state Department [00:03:21] Worth alks about recruitment and training of Peace Corp Volunteers for Thailand [00:04:00] Interviewer asks how many of these students are at Cal Poly [00:05:04] Interviewer asks about the benefits of these overseas programs [00:06:02] Interviewer begins to wrap up interview